Marketing - Solomon, Michael R. (Pearson, 2016)
Marketing: Real People, Real Choices, Global Edition Description Real People, Real Choices Marketing: Real People, Real Choicesis the only text to introduce marketing from the perspective of real people who make real marketing decisions at leading companies everyday. Timely, relevant, and dynamic, this reader-friendly text shows students how marketing concepts are implemented, and what they really mean in the marketplace. The Eighth Edition features a completely reorganized Table of Contents and chapter pedagogy divided in a four-part structure that emphasizes the value proposition and the process of creating and delivering value. This edition presents more information than ever on marketing research and analytics and students are guided through chapter content with new integrated study maps and assessments that help them actively learn and retain content